2017
DOI: 10.1126/scisignal.aak9660
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the ubiquitylation and deubiquitylation of CREB-binding protein modulates histone acetylation and lung inflammation

Abstract: Cyclic adenosine monophosphate (cAMP) response element–binding protein (CREB)–binding protein (CBP) is a histone acetyltransferase that plays a pivotal role in the control of histone modification and the expression of cytokine-encoding genes in inflammatory diseases, including sepsis and lung injury. We found that the E3 ubiquitin ligase subunit FBXL19 targeted CBP for site-specific ubiquitylation and proteasomal degradation. The ubiquitylation-dependent degradation of CBP reduced the extent of lipopolysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…F-box protein, a component of SCF E3 ligase complex, can specifically recognize substrates (5,7,9). We have demonstrated that FBXL19 played an antiinflammatory role by targeting IL-33 receptor (ST2L) (13) and a histone acetyltransferase (CBP) (14). Further, a role of FBXL19 in the regulation of ubiquitination of Rho GTPases, such as RhoA (16), Rac1 (17), and Rac3 (15), has been revealed.…”
Section: Cbp Regulates Fbxl19 Acetylation and Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…F-box protein, a component of SCF E3 ligase complex, can specifically recognize substrates (5,7,9). We have demonstrated that FBXL19 played an antiinflammatory role by targeting IL-33 receptor (ST2L) (13) and a histone acetyltransferase (CBP) (14). Further, a role of FBXL19 in the regulation of ubiquitination of Rho GTPases, such as RhoA (16), Rac1 (17), and Rac3 (15), has been revealed.…”
Section: Cbp Regulates Fbxl19 Acetylation and Stabilitymentioning
confidence: 99%
“…We have shown that CBP is a substrate of SCF FBXL19 E3 ligase (14). Overexpression of FBXL19 reduces CBP stability and mitigates CBP-mediated histone acetylation (14).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Indeed, phosphorylation of Usp14 (or the use of a Usp14 phosphomimetic) results in increased activity in assays with the fluorogenic substrate ubiquitin-7-amino-4-methylcoumarin (Ub-AMC), for both Usp14 in isolation and Usp14 in the proteasome, suggesting that phosphorylation and proteasome binding activate Usp14 via unrelated mechanisms [73]. Usp14 activity is elevated in LPS-treated-cells, in parallel with its phosphorylation, possibly by AKT [74,75]. These and other observations suggest an anti-inflammatory effect of Usp14 inhibition [7478].…”
Section: Enzymatic Activity and Its Regulationmentioning
confidence: 99%
“…Since the original study on IU1, several groups have reported proteins that show accelerated degradation under IU1 treatment, including the Prion protein PrP [102,103], cGAS [108], phosphorylated tyrosine hydroxylase [104], the androgen receptor [105], vimentin [106], aurora kinase [111], CREB-binding protein [75], YFP-tagged CD3δ [107], and the model UPS substrate GFP u [107]. In many of these studies, the on-target nature of the IU1 effect is supported by genetic confirmation [102,105108].…”
Section: Effects Of Deubiquitination On Substrate Degradationmentioning
confidence: 99%